2006
DOI: 10.1002/pssc.200567027
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation conductivity analysis on the Bi‐based superconductors processed under same conditions

Abstract: We report electrical conductivity fluctuation measurements on different Bismuth-based granular samples synthesized under same processing conditions.Using the fluctuation conductivity ∆σ as a function of the reduced temperature ε in the range -7 < lnε < 1, we identified Gaussian and critical fluctuation conductivity in (Bi,Pb)-2223 and Bi-2212 samples. Within the mean field region, samples show predominately two dimensional (2D) behaviour with exponent λ = − 1. Closer to critical temperature T C , we have obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…The value of d (= effective length in the direction perpendicular to the current flow defining the effective layer thickness of the 2D-system) with 11.6 nm is smaller than that obtained in Reference [65] with 19 nm (polycrystalline Bi-2212 samples) and for Bi-2212 single crystals [62]. This may point to a squeezing of the Cu-O-layers, which is understandable when regarding the large surface contribution in the present nanometer-sized fibers (see also Figure S4 in the Supplementary Materials).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The value of d (= effective length in the direction perpendicular to the current flow defining the effective layer thickness of the 2D-system) with 11.6 nm is smaller than that obtained in Reference [65] with 19 nm (polycrystalline Bi-2212 samples) and for Bi-2212 single crystals [62]. This may point to a squeezing of the Cu-O-layers, which is understandable when regarding the large surface contribution in the present nanometer-sized fibers (see also Figure S4 in the Supplementary Materials).…”
Section: Discussioncontrasting
confidence: 62%
“…Several types of Bi-2212 samples were already analyzed by means of excess conductivity/fluctuation-induced conductivity in the literature. This comprises single crystals [62] polycrystalline bulks [63][64][65], polycrystalline Bi-2212 doped with Ni, La [66][67][68], and Bi-2212 thin films [69]. Several authors found the missing 1D fluctuation regime in their Bi-2212 samples, and a similar observation was made when studying the Y-358 compound [70].…”
Section: Discussionmentioning
confidence: 68%
“…The value of the proportionality coefficient K in the above equations is 0.12 [22]. By using N G for Cu 0.…”
Section: Resultsmentioning
confidence: 98%
“…[21][22][23] These two theories AL and LD are directly contributing to the excess conductivity which help us to study the dimensionality of fluctuations of superconductivity.…”
Section: Theoretical Models For Analysis Of Experimental Datamentioning
confidence: 99%